Acaricidal Mechanism of Scopoletin Against Tetranychus cinnabarinus - Zhou, Hong; Zhang, Yong-qiang; Lai, Ting; Liu, Xue-jiao; Guo, Fu-you; Guo, Tao; Ding, Wei (Frontiers in Physiology, 2019)
Scopoletin is a promising acaricidal botanical natural compound against Tetranychus cinnabarinus, and its acaricidal mechanism maybe involve calcium overload according to our previous study. To seek potential candidate target genes of calcium overload induced by scopoletin in T. cinnabarinus, RNA-seq was utilized to detect changes in transcription levels. 24 and 48 h after treatment, 70 and 102 differentially expressed genes were obtained, respectively. Target genes included 3 signal transduction genes, 4 cell apoptosis genes, 4 energy metabolism genes, and 2 transcription factor genes. The role of 3 calcium signaling pathway-related genes, namely, G-protein-coupled neuropeptide receptor, Bcl-2 protein and guanylate kinase (designated TcGPCR, TcBAG, and TcGUK, respectively) in the calcium overload were investigated in this study. RT-qPCR detection showed that scopoletin treatment upregulated the expression level of TcGPCR and downregulated the expression level of TcBAG and TcGUK. The result of RNAi indicated that downregulation of TcGPCR decreased susceptibility to scopoletin, and downregulation of TcBAG and TcGUK enhanced susceptibility to scopoletin. Functional expression in Chinese hamster ovary cells showed that scopoletin induced a significant increase in intracellular free calcium [Ca2+]i levels by activating TcGPCR. These results demonstrated that the acaricidal mechanism of scopoletin was via disrupting intracellular Ca2+ homeostasis and calcium signaling pathway mediated by GPCR, BAG and GUK.